Brexit and Procurement Law - Maddox, Catherine; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Public procurement law, regulating public sector purchasing of certain contracts for goods, works and services, is an area of EU law which is closely intertwined with the UK's economy. It will almost inevitably be affected by the consequences of Brexit.At a time of significant uncertainty, this book explores policy directions which domestic procurement law could take in the future, including whether 'Buy National' policies might feasibly be introduced, or whether existing procurement procedures could be significantly reviewed.
Abbreviations and definitionsIntroductionHow to use this bookPart I Challenges and OpportunitiesChallengesLegal and political context for the future of procurement lawCurrent legal framework for procurement lawEuropean Union Withdrawal Act and procurement law UK government statements on procurement law policyGovernment White Paper and procurement lawEuropean Commission Communication impact of the no deal scenario on procurement lawThe Irish Border and its impact on procurement lawEuropean Commission Draft Withdrawal Agreement ("DWA") and procurement lawDraft Withdrawal Agreement key provisions Analysis of Draft Withdrawal Agreement key provisionsContracts subject to the EU procurement regime after the Transition PeriodProcurement procedures ongoing at the end of the Transition PeriodDraft Withdrawal Agreement and equality under procurement law Draft Withdrawal Agreement and modification of existing contractsProcurement complaints under the Draft Withdrawal Agreement Looking into the futureLosing access to EU online tools, universal classification systems and other guidanceeCertis and the European Single Procurement DocumentOJEU advertisingCommon Procurement Vocabulary codesLoss of EU Directive 2014/24 and 2014/23 recitalsTimelineReduction of access to procurement markets International procurement instrumentPracticalities of reduced competitionOpportunitiesPotential trading models and their impact on UK procurementTrading models summaryExisting trading models and their impact on EU-UK procurement lawPotential future trade agreements and their procurement law implicationsEEA and EFTA state procurement modelEEA membership and the UK's current membership statusEEA membership and the UK's future membership statusEEA procurement regulation and key principlesEEA procurement regulation and preliminary referencesEEA procurement regulation and control over new legislationEFTA procurement modelTrade arrangementsProcurement regulationCanadian procurement model Trade arrangementsProcurement regulationWorld Trade Organisation- Government Procurement Agreement modelGovernment Procurement Agreement Trade ArrangementsGovernment Procurement Agreement and its impact on UK procurementGovernment Procurement Agreement procedural requirementsGovernment Procurement Agreement dispute settlement mechanismsGovernment Procurement Agreement and UK membershipUkraine's procurement modelTurkey's procurement modelFavouring national suppliers and the 'Buy British' campaignCase study: Buying British: HarmonCase study: Buying British: Contract award for manufacture of British passportsCase study: Buy Australian: Australia's accession to the GPABuying British: The Equality Act 2010Artificial narrowing of technical specifications to favour national suppliersEU view on discriminatory procurement policiesPotential revisions of the procurement regimePotential revisions of the procurement regime - simplifying the current procurement systemPotential revisions of the procurement regime - below threshold contractsPotential revisions of the procurement regime - remedies regime after BrexitRemedies regime after Brexit - fast track or tribunal processRemedies regime after Brexit - Shorter and Flexible Trials pilot schemeRemedies regime after Brexit - remedies reviewRemedies regime after Brexit - remedies systems in other EU member statesRemedies regime after Brexit - equalityThe future of procurement lawProcurement law during the Transition PeriodProcurement law after the Transition PeriodProbable direction of procurement lawPart II Key Legislation and Recommended ReadingAnnex I: Summary DashboardKey pieces of legislationRecommended reading Source acknowledgements Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: Brexit; Procurement; public procurement; UK procurement law; UK procurement reform; Government purchasing -- Law and legislation -- Great Britain; Government purchasing -- Law and legislation -- European Union countries; Public contracts -- Great Britain; Public contracts -- European Union countries; Government purchasing -- Law and legislation; Public contracts; Electronic books